Peran Kepala Madrasah dalam Meningkatkan Mutu Pendidikan (Studi Kasus di MTs. Swasta Sidikalang) - Nelly Nelly (Hikmah, 2022)
This study aims to analyze the role of the principal in improving the quality of education in MTS. Islamic education. The focus of the study is on two things, namely the efforts of the principal in improving the quality of education, and the opportunities and obstacles of the principal in improving the quality of education. This research began with the problem of declining teacher performance, which was based on initial observations due to the lack of good quality management in the school. The research method used is qualitative with a case study approach. Research informants are principals, teachers, and students. Data collection techniques through observation, interviews, and documentation studies. The results of the study indicate that the efforts made by teachers go through the quality assurance cycle, namely Determination, Implementation, Implementation Evaluation, Implementation Control, and Improvement. The cycle starts from policy determination, policy implementation, evaluation of policies that have been applied, control over policies that have been realized, and follow up on evaluation results. Opportunities in improving quality can be seen from the competence of the principal, teacher motivation, and the synergy of cooperation. While the obstacles faced are the limitations of teachers in mastering learning technology so that it hampers the principal's program in terms of digitizing education.